The Influence of National Economy Specifics on the Interaction between Universities and Corporations in the Field of Innovation - G. Gribov, Pavel; L. Lomakin, Andrey; Ya. Kurganskaya, Marina; Z. Kumelashvili, Maria (International Journal of Criminology and Sociology, 2022)
Questions of the influence of national economy features on innovation activity do not lose their relevance at the beginning of the XXI century. In different countries of the world, new approaches to stimulating innovation are emerging that take into account the peculiarities of national economies. However, the main problem of such activities remains the speed of movement of new technologies from universities to corporations and the further creation of new products and technologies. The number of patents obtained by various organizations is becoming one of the main indicators of the development of the national economy. It is noted that the relationship between research costs and the number of patents obtained is not as linear as it seems in theory. The practical implementation of diffuse processes in an innovative environment also does not have a linear dependence on the "investment – result". The use of statistical analysis methods allowed us to identify the facts that signal that the model of stimulating innovation activity, formed in the 1980s of the XX century, is losing its advantages. The article examines in detail the progress of higher education reform in the EU countries and identifies the key features of combining scientific organizations to create large multidisciplinary research centers. The authors conclude that the experience of such a reform in France is very interesting to study in Russia. It is noted that since the 2000s. in the United States and the European Union, questions are raised about the revision of the University tax system, as well as changes in the legal status of educational organizations. Similar trends occur in Russia, however, due to historical and social processes, they have their specifics. According to the authors, the regulation of taxation of scientific activities leads to the formation of unique elements of the economic mechanism for stimulating innovation.